Development of the Japanese Version of the Rape Excusing Attitudes and Language Scale and Comparison Between Rape Myth Acceptance in Japan and the U.S - Sasaki, Rina (Journal of interpersonal violence, 2025)
Rape myth acceptance (RMA) is the acceptance of false beliefs, stereotypes, and statements about rape victims, perpetrators, and the act itself. RMA positively predicts shame felt by victims and negatively predicts reports of sexual victimization. Knowledge about sexual violence changes over time; accordingly, psychometric scales measuring RMA should be updated. Hahnel-Peeters and Goetz developed the Rape Excusing Attitudes and Language (REAL) scale by updating the Illinois RMA Scale—a major instrument used in the United States. However, the REAL scale is not available in Japanese. Therefore, we developed and validated a Japanese version of the REAL scale, evaluated RMA in Japanese individuals (N = 1,000), and compared the Japanese participants’ RMA levels with the mean participant scores from Hahnel-Peeters and Goetz. In collaboration with one of the original authors, the Japanese version was developed through a back-translation process and administered to 1,000 men and women aged between 18 and 65; exploratory and confirmatory factor analyses were conducted on the data collected. The confirmatory factor analysis showed that the Japanese version moderately fitted the 4-factor structure of the original REAL scale. However, a 2-factor form obtained in the exploratory factor analysis best fit the data. Consistent with the original version, the Japanese version showed higher RMA in men than in women. The young generation (18–29 years old) self-reported higher RMA than other generations. Japan’s RMA was significantly higher than that of the U.S. sample. The Japanese version of the REAL scale can be used in future studies to assess RMA in Japanese individuals and develop suitable educational programs to reduce RMA.